Risk Factors of Anemia in Children Age 6 Months to 5 Years Presenting to Qazi Hussain Ahmad Medical Complex - Ibadullah; Khan, Irfan; Qayyum, Mahnoor (Indus Journal of Bioscience Research, 2025)
Background: Anemia in children is a significant public health problem, particularly in developing countries, where it adversely affects physical, cognitive, and social development. This study aims to identify the key risk factors contributing to anemia in children aged 6 months to 5 years presenting to Qazi Hussain Ahmad Medical Complex, Nowshera. Methods: This cross-sectional study was conducted over six months, including 135 children with anemia. ‘Participants were recruited using a non-probability consecutive sampling technique’. ‘Data were collected through structured interviews with mothers, focusing on maternal, socioeconomic, and child-related factors’. Information on maternal age, education, inter-pregnancy intervals, breastfeeding practices, socioeconomic status, and recent child morbidity (e.g., diarrhea) was recorded. Data were analyzed using IBM SPSS version 23, with chi-square tests applied to evaluate the association between risk factors and anemia severity. A p-value ≤ 0.05 was considered statistically significant. Results: The most prevalent risk factors for anemia were poor socioeconomic status (59.3%), low maternal education (55.6%), and poor breastfeeding practices (44.4%). Other significant factors included short inter-pregnancy intervals (37.0%), younger maternal age (<24 years; 31.1%), and recent diarrhea episodes (22.2%). These factors were significantly associated with the severity of anemia, with p-values ≤ 0.05 for all associations. Conclusion: The economic status of the family, maternal factors, and the child’s health all influence the occurrence of anemia in early childhood. Public health initiatives of the government, in combination with the educational campaigns directed towards mothers and better overall health facilities, can greatly mitigate the childhood anemia burden.